2005
DOI: 10.1212/01.wnl.0000154516.43630.c5
|View full text |Cite
|
Sign up to set email alerts
|

Increased rate of major malformations in offspring exposed to valproate during pregnancy

Abstract: Maternal exposure to valproic acid during the first trimester of pregnancy significantly increased the risk of major malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
199
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(217 citation statements)
references
References 42 publications
(37 reference statements)
10
199
1
7
Order By: Relevance
“…This demonstrates a highly specific developmental function (Haberland et al, 2009). Consequently, it has been reported that mothers who take the HDAC inhibitor valproic acid during the first trimester of pregnancy have a significantly increased risk of their fetuses developing craniofacial abnormalities Wyszynski et al, 2005). Even though HDAC1 seems to be no essential for cranial NC differentiation, studies in zebrafish demonstrated the requirement of this protein for the proper repression of the transcription factor FoxD3 necessary for the mitfadependent melanophore development (Ignatius et al, 2008).…”
Section: Acetylationmentioning
confidence: 99%
“…This demonstrates a highly specific developmental function (Haberland et al, 2009). Consequently, it has been reported that mothers who take the HDAC inhibitor valproic acid during the first trimester of pregnancy have a significantly increased risk of their fetuses developing craniofacial abnormalities Wyszynski et al, 2005). Even though HDAC1 seems to be no essential for cranial NC differentiation, studies in zebrafish demonstrated the requirement of this protein for the proper repression of the transcription factor FoxD3 necessary for the mitfadependent melanophore development (Ignatius et al, 2008).…”
Section: Acetylationmentioning
confidence: 99%
“…Although there have been studies from as early as the 1960s suggesting links between major congenital malformations (MCMs) and the use of AEDs during pregnancy [6][7][8][9], the advent of the large prospective, albeit observational, epilepsy and pregnancy registries have recently added much information on the relative risks associated with the individual AEDs [5,[10][11][12][13][14][15][16][17]. The key to a successful outcome in this respect is knowledge of the individual risks and imparting these risks through preconceptual counseling, enabling women to make informed choices and allowing any alteration in therapy to be made prior to pregnancy.…”
Section: Preconceptual Counselingmentioning
confidence: 99%
“…A common theme emerging from the preliminary data from epilepsy and pregnancy registers is that sodium valproate appears to carry an elevated risk of MCM and perhaps neurodevelopmental delay compared with other AEDs [10,12,13,[15][16][17].…”
Section: Preconceptual Counselingmentioning
confidence: 99%
See 2 more Smart Citations